ダイ17ジ ナンキョク チイキ カンソクタイ カイヨウ ブモン ホウコク - 柴山, 信行; シバヤマ, ノブユキ; 大庭, 幸弘; オオニワ, ユキヒロ; Shibayama, Nobuyuki; Ohniwa, Yukihiro (国立極地研究所, 1977)
P(論文) 第17次南極地域観測において,定常観測(1975-1976)として海上保安庁水路部の担当した海洋観測および潮汐の結果を報告する. This report presents the results of the oceanographic observations, which were carried out by the 17th Japanese Antarctic Research Expedition in 1975-1976. departmental bulletin paper